European Code against Cancer 4th Edition: Obesity, body fatness and cancer. (December 2015) - Anderson, Annie S.; Key, Timothy J.; Norat, Teresa; Scoccianti, Chiara; Cecchini, Michele; Berrino, Franco; Boutron-Ruault, Marie-Christine; Espina, Carolina; Leitzmann, Michael; Powers, Hilary; Wiseman, Martin; Romieu, Isabelle
Abstract: It is estimated that over half the population of the European Union (EU) is overweight or obese due to an imbalance between energy expenditure and energy intake; this is related to an obesogenic environment of sociocultural, economic and marketing challenges to the control of body weight. Excess body fat is associated with nine cancer sites – oesophagus, colorectum, gall bladder, pancreas, postmenopausal breast, endometrium, ovary, kidney and prostate (advanced) – and 4–38% of these cancers (depending on site and gender) can be attributed to overweight/obesity status. Metabolic alterations which accompany excess body weight are accompanied by increased levels of inflammation, insulin, oestrogens and other hormonal factors. There are some indications that intentional weight loss is associated with reduced cancer incidence (notably in postmenopausal breast and endometrial cancers). Excess body weight is also a risk factor for several other diseases, including diabetes and heart disease, and is related to higher risk of premature death. In reviewing the current evidence related to excess body fat and cancer, the European Code against Cancer Nutrition Working Group has developed the following recommendation: 'Take action to be a healthy body weight'.